Factors affecting the choice of elementary school for children among parents in the municipalities of Leganes, Oton and Pavia. - Araneta, Arlyn Gavieta
This paper was designed to identify the factors that significantly affect the choice of elementary school for children among parents in the municipalities of Leganes, Oton and Pavia. A logistic Regression Analysis was employed so as to identify the significant factors. Descriptive analysis showed that the majority of the households have children enrolled in private than in public schools (54% vs. 46%). At 1% level of significance, the model showed that school quality reflected by the computer subject offered by the school, the school distance measured by the travel time going to school, and the school as either parent's alma mater were significant factors affecting parents decision for an elementary school for the children